RISK MAPPING IN URBAN AREAS: METHODOLOGICAL ESSAY FOR SAMPLE AREA OF SANTOS, SÃO PAULO - BRAZIL - de Freitas, Maria Isabel Castreghini; Rossetti, Lucimari Aparecida Franco Garcia; de Oliveira, Rodrigo Buchianeri Numa (Revista Brasileira de Cartografia, 2015)
The mapping of densely urbanized areas is a constant challenge for cartographers and Geoscience professionals that rely on techniques of Digital Cartography and Geographic Information Systems (GIS), mainly due to the high concentration of buildings and the presence of varied urban occupation, housing people from different social statements in confined and reduced urban spaces, which makes difficult the mapping. Currently, there are many studies dealing with the vulnerability and risks supported by Geo-technology. In order to contribute to methodological reflections on the theme, this study proposes to apply established methodologies of Principal Components Analysis (PCA) and Multi-Criteria analysis (MCA), based on SPSS programs and ArcGIS r. 10.2, aiming to integrate thematic maps for studies of vulnerabilities and risks of mass movement in the sample area selected in Santos, SP-Brazil. The methodological procedure corresponded to the different integration techniques supported in Geo-technology, such as the mapping of the Urban Land Use based on interpretation of orthorec-tified images, the Slope based on 10 m contour lines and the Socio-environmental Vulnerability held by Factor Analysis (FA). The integration of thematic data by Multi-criteria Analysis (MCA) generated a synthesis map of the risk areas, accompanied by the quantitative analysis of the different thematic classes. It can be concluded that the methodology applied brought a qualitative contribution to traditional risk mappings in the area, especially with the contribution of the Land use data and the Socio-environmental vulnerability.